Keaktifan Belajar Siswa Di Tinjau Dari Minat Belajar Dan Partisipasi Dalam Interaksi Edukatif Pada Siswa Kelas Viii Mata Pelajaran Ilmu Pengetahuan Sosial Di Smp Islam Kedung Kabupaten Jepara Tahun Ajaran 2016/2017 - Fitriyanto, Bayu Dwi, Drs. Muhammad Yahya, M.Si (2017)
The purpose of this research is to find out: 1) the influence of the interest of students towards active learning students in junior high school of Islam, Kedung Jepara Regency. 2) Influence participation in educational interactions toward active learning students in junior high school of Islam, Kedung Jepara Regency. 3) Influence the learning interest and participation in educational interactions toward active learning students in junior high school of Islam, Kedung Jepara Regency. This research included quantitative types of associative research with the withdrawal of the conclusion through statistical analysis. The population in this research is the whole Islamic junior high school students Kedung, Jepara Regency. samples taken as many as 105 is propotional students with random sampling. Required data obtained via the question form and documentation. Previously the now tested cobakan and tested the validity and tested reliability. Data analysis technique used was multiple linear regression analysis, t-test, F-test, and the relative contribution and effective. The results of the regression analysis regression line equation is obtained: Y = 9,513 + 1,139 X1 + 0,943 X2. The equation shows that learning may be influenced by the interest in learning and participation in educational interaction. The conclusions drawn are: 1) the influence of interest learning towards the learning of junior high school students in the liveliness of Islam Kedung, Jepara Regency is acceptable. It is based on binary linear regression analysis (test t) Note that thitung > ttabel, 5.935 > 2.000 and value its significance, i.e. 0.05 < 0.000 with the relative contributions of 52% and an effective contribution of 31,8%. 2) Influence participation in educational interactions toward active learning students in junior high school of Islam Kedung, Jepara Regency acceptable. It is based on binary linear regression analysis (test t) Note that thitung > ttabel, namely 5.565 > significance and value 2.000 < 0.05, i.e. the relative contributions of 0.000 48% and 29.3% effective contribution. 3) learning Interest and participation in educational interaction together against the liveliness of student learning in junior high school of Islam Kedung acceptable. This is based on the analysis of binary linear regression variansi (test F) note that Fhitung > Ftabel, namely 80.028 > 3.150 and value its significance in jun, i.e. 0.05 < 0.000.4) the coefficient of determination (R2) of 0.611 shows that the magnitude of the interest in learning and participation in educational interactions toward active learning students ior high school of Islam is 61,1% Paul, while the rest is affected by other variables.